Pendapingan Penguatan Sistem Kelompok Tani Dalam Meningkatkan Pendapatan Masyarakat: Khameyaka, Distrik Ebungfa, Kabupaten Jayapura - Daniel Ayub Dawan; Eduard Yohannis Tamaela (JOURNAL INNOVATION AND COMMUNITY SERVICE, 2021)
One method of resolving poverty is to empower society in order to improve the community's revenue. Natural resources provide a significant contribution to societal wealth and growth. Agricurtural is a natural resource with a lot of promise. Indonesia is an agrarian country, which means that it has a lot of potential and a lot of resources that are suitable for agriculture. However, there are a variety of issues that farmers encounter, and women and housewives are no exception. In general, women are compelled to work and earn a wage because of the economic demand produced by their husband's poor earnings, which cannot meet the requirements. The family's economic issues will force the ladies to take on roles that do not rely on their husband's earnings. The qualitative approach method was used in this study. Data was collected using the observation interview approach, and documentation was used to confirm the validity of the data, utilizing the persistence in field technique and triangulation of source and method. In this study, data was analyzed utilizing an interactive model, which included data collection, data reduction, data display, and conclusion. The findings revealed that women farmer organizations have a role in raising earnings from agricultural products, while waste banks play a part in improving productivity by using yard area. They also play a role in increasing education and knowledge through frequent meetings and coaching. The member will be able to raise his or her earnings and meet his or her daily needs as a result of these actions. Each member can utilize the proceeds from KUD Mandiri's activities to meet their daily needs.